Carbapenem‑resistant Enterobacteriaceae in the livestock, humans and environmental samples around the globe: a systematic review and meta‑analysis - Tuhamize, Barbra; Bazira, Joel (Scientific Reports, 2024)
Carbapenem‑resistant Enterobacteriaceae (CRE) have diminished treatment options causing serious morbidities and mortalities. This systematic review and meta‑analysis assessed the prevalence and associated factors of Enterobacteriaceae infections in clinical, livestock and environmental settings globally. The population intervention comparison and outcome strategy was used to enroll studies using the preferred reporting system for systematic review and meta‑analysis to include only cross‑ sectional studies. Search engines used to retrieve articles included journal author name estimator, PubMed, Google Scholar and African Journals Online (AJOL). The Newcastle–Ottawa scale was used to assess the quality of studies. Sixteen articles from 2013 to 2023 in Africa, Asia, Europe and South America were studied. The pooled prevalence of CRE was 43.06% (95% CI 21.57–66.03). Klebsiella pneumoniae (49.40%), Escherichia coli (26.42%), and Enterobacter cloacae (14.24%) were predominant. Klebsiella pneumoniae had the highest resistance with the blaKPC‑2 in addition to blaNDM, blaOXA‑48, blaIMP and blaVIM. The blaKPC‑2 genes occurrence was associated with environmental (P‑value < 0.0001) and South American studies (P‑value < 0.0001), but there was no difference in the trends over time (P‑value = 0.745). This study highlights the high rates of CRE infections, particularly within blaKPC production. Monitoring and surveillance programs, research and infection control measures should be strengthened. Additionally, further studies are needed to explore the mechanisms driving the predominance of specific bacterial species and the distribution of resistance genes within this bacterial family.
Keywords: Enterobacteriaceae; Carbapenem-resistance; Resistance genes